2014
DOI: 10.1039/c3np70115h
|View full text |Cite
|
Sign up to set email alerts
|

Strategies towards the synthesis of calyciphylline A-type Daphniphyllum alkaloids

Abstract: The Daphniphyllum alkaloids are a diverse family of natural products rich in number and structural diversity that have been known for many decades. However, the structurally unique subclass of calyciphylline A-type alkaloids has only recently been discovered and is relatively unexplored. Several noteworthy core syntheses and the development of a wide range of novel synthetic strategies have been achieved. This includes strategies based on intramolecular Michael addition, Pd-catalysis, cycloaddition, and Mannic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(48 citation statements)
references
References 85 publications
0
48
0
Order By: Relevance
“…The organic extract was dried, concentrated, and purified by chromatography (hexane/AcOEt, 99 : 1!75 : 25) to give β-keto ester 1d (1.3 g, 5.3 mmol, 84 %) as a yellow oil. 1 3 ). 13 C-NMR (100 MHz, CDCl 3 ): 207.9 (C(1)); 172.5 (CO 2 Et); 109.4 (C(5)); 64.5 and 64.3 (OCH 2 ); 61.4 (OCH 2 ); 58.7 (C(2)); 37.0 (C(7)); 36.5 (C(4)); 34.1 (C(3)); 29.3 (C(6)); 14.0 (CH 3 C(1)); 172.9 (CO 2 Et); 109.4 (C(5)); 64.5 and 64.3 (OCH 2 ); 61.2 (OCH 2 ); 58.8 (C(2)); 36.4 (C(7)); 34.3 (C(4)); 33.9 (C(3)); 30.2 (C (6) Benzyl-2,2,2-trichloro-N-(9-methyl-1,4-dioxa…”
Section: -Methyl-14-dioxaspiro[46]undecan-8-one (1c)mentioning
confidence: 99%
See 3 more Smart Citations
“…The organic extract was dried, concentrated, and purified by chromatography (hexane/AcOEt, 99 : 1!75 : 25) to give β-keto ester 1d (1.3 g, 5.3 mmol, 84 %) as a yellow oil. 1 3 ). 13 C-NMR (100 MHz, CDCl 3 ): 207.9 (C(1)); 172.5 (CO 2 Et); 109.4 (C(5)); 64.5 and 64.3 (OCH 2 ); 61.4 (OCH 2 ); 58.7 (C(2)); 37.0 (C(7)); 36.5 (C(4)); 34.1 (C(3)); 29.3 (C(6)); 14.0 (CH 3 C(1)); 172.9 (CO 2 Et); 109.4 (C(5)); 64.5 and 64.3 (OCH 2 ); 61.2 (OCH 2 ); 58.8 (C(2)); 36.4 (C(7)); 34.3 (C(4)); 33.9 (C(3)); 30.2 (C (6) Benzyl-2,2,2-trichloro-N-(9-methyl-1,4-dioxa…”
Section: -Methyl-14-dioxaspiro[46]undecan-8-one (1c)mentioning
confidence: 99%
“…After cooling to room temperature, the mixture was filtered by passage through a plug of Na 2 SO 4 with benzene and concentrated to give the corresponding enamido ester 1d' (683 mg, quantitative yield) as a yellow solid. 1 To a solution of 1d' (682 mg, 2.9 mmol) in CH 2 Cl 2 (8 mL) containing Et 3 N (800 μl, 5.8 mmol), was added dropwise Cl 3 CCOCl (640 μl, 5.8 mmol) in CH 2 Cl 2 (1.8 ml) at 0°C. After heating at reflux temperature for 24 h, the mixture was concentrated, redissolved in CH 2 Cl 2 , and washed with aqueous 1 N HCl, and brine.…”
Section: Ethyl 9-[benzyl(trichloroacetyl)amino]-14-dioxaspiro[46]unmentioning
confidence: 99%
See 2 more Smart Citations
“…[1] These Daphniphyllum alkaloids show structural diversity and are classified into 14 structural types based on their characteristic ring systems.Daphenylline (1), isolated from the fruit of D. longeracemosum by Hao and co-workers in 2009, is the first member of the Daphniphyllum alkaloids that contains ab enzene ring in the core structure ( Figure 1). [2] Daphenylline includes ar earranged 22-norcalyciphylline At ype skeleton, [3] the highly fused hexacyclic system of which has attracted significant attention in the chemical community.W hile several synthetic studies have been reported to date, [4,5] Li and co-workers recently accomplished the first total synthesis of (À)-daphenylline.…”
mentioning
confidence: 99%